PENGARUH PENGGUNAAN MEDIA GAMBAR TERHADAP KEMAMPUAN MENULIS KARANGAN DESKRIPSI SISWA KELAS IX SMP PGRI 3 BANDAR LAMPUNG - Hastuti Hastuti; Frieska Maryova Rachmasisca (LPPM STKIP PGRI Bandar Lampung, 2021)
This study aims to determine the influence of image media on students' writing skills. The research method used in this research is experimental research. The results of the ANOVA calculation above show that Fcount = 18.78* which is greater than Ftable = 4.08 at a = 0.05 and Fcount at a = 0.01. The obtained value of Fcount = 31.23 which is greater than Ftable = 4.08 at a = 0.05 and Ftable = 7.31 at a = 0.01. This means Ho is rejected. Obtained 9.18 and Ttable = 6.038 for T(0.05) = 6.038 T (0.01) = 2.750 turns To > Ttable . Ho is rejected and H1 is accepted. There is an influence of low learning independence on students who have high learning independence between the application of image media and those who do not apply image media, namely by looking at the results of To = 1.16 < T table = 6.038; Ho is rejected.